India-US relations in the age of uncertainty an uneasy courtship - Jain, B. M. (Rethinking Asia and international relations, 2016)
In the initial phase of the Obama administration, India's ruling class and strategic community formed a perception that the spirit of strategic partnership between the two countries might be diluted on account of China looming large in the priorities of this administration. Despite occasional hiccups in their relationship, this perception was overshadowed by the administration's recognition of India's role as counterweight to China in the Asia-Pacific region. This book addresses and re-evaluates the perceptions, policies and perspectives of public policy makers and bureaucratic elites in both India and the US in setting and articulating the tone, tenor and substance of the multi-faceted ties between the two countries. The scope of the book is not exclusively limited to the bilateral relationship in the critical areas such as the Indo-US nuclear deal, defence, security and strategic partnership. Its concerns and ramifications are much wider in global and regional contexts, covering/involving security architecture in the Asia-Pacific region, the interface between terrorism and weapons of mass destruction (WMDs), China as a factor in India-US relations, and the fallout of the New Delhi-Washington partnership on South Asia.